The World Capitalist Crisis, Latin America and Ecuador: Socialism of the 2ist Century or Progressive Neoextractivism? - Ramírez Bonilla, Diego Alejandro (Sociedad y Economía, 2015)
This article makes a characterization report on the global capitalist crisis, its most recent expression in the financial system after the bubble of 2008 and its impact on Latin American economies, emphasizing on the analysis of the Citizen Revolution of Ecuador and the role of this country in the global economy in light of the requirements of in- ternational capital. The relation between the process led by Rafael Correa and capital appreciation during the worldwide economic crisis, as well as its connection to the so- called emerging powers is analyzed. Finally, there are arguments provided that contra- dict the characterization of this process as an aspect of “Socialism of the 21st Century”, highlighting its features as a form of neoextractivism.